If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (7b + -6) + -3(2b + 4) = -3 Reorder the terms: (-6 + 7b) + -3(2b + 4) = -3 Remove parenthesis around (-6 + 7b) -6 + 7b + -3(2b + 4) = -3 Reorder the terms: -6 + 7b + -3(4 + 2b) = -3 -6 + 7b + (4 * -3 + 2b * -3) = -3 -6 + 7b + (-12 + -6b) = -3 Reorder the terms: -6 + -12 + 7b + -6b = -3 Combine like terms: -6 + -12 = -18 -18 + 7b + -6b = -3 Combine like terms: 7b + -6b = 1b -18 + 1b = -3 Solving -18 + 1b = -3 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 18 + 1b = -3 + 18 Combine like terms: -18 + 18 = 0 0 + 1b = -3 + 18 1b = -3 + 18 Combine like terms: -3 + 18 = 15 1b = 15 Divide each side by '1'. b = 15 Simplifying b = 15
| 1/3x^2-1/18x-11/9=0 | | -2(k+16)=-44 | | e^2k=6 | | 15=-7+9(v-6) | | 30(1/2) | | 21k^2+11k-2=0 | | y=-4*-2-5 | | 30*1/2 | | y=-4*1-5 | | 4x+14=-11x-2 | | 0.5(x+8)=-12 | | 2x+1x^2+8=0 | | 3x=6-6 | | 2x-1x^2+8=0 | | 2x+8-1x^2=0 | | 6/7x4/9 | | 1/x-x=0 | | 2ln(x+3)+1=0 | | 5m+11=3(m+1) | | 4/3=q/9 | | -5-3/9-2 | | 1/x-x0 | | 9x+9=3x+6 | | 1/2=q/6 | | 2x^3-5x^2+3x-1=0 | | n+6=13-6n | | X+62+62=180 | | 3x-6x+3x=8+15-12 | | Sinx+cosx=0.5 | | 4x+5x-3x=12 | | sin(3y-50)-cos(2y+10)=0 | | 165/605 |